Jeffrey Eugenides “the virgin suicides” and the convergence of literary, psychological, and social discourses on suicide - Shukurova Sabokhat Odilovna (International Journal Of Literature And Languages, 2025)
This article critically examines the representation of suicide in Jeffrey Eugenides’s The Virgin Suicides, analyzing the text as a literary work that interweaves psychological despair, social alienation, and aesthetic ambiguity. Through a close reading of narrative structure, thematic motifs, and symbolic imagery, the study explores how the novel reflects broader cultural preoccupations with suicide and the disintegration of social order. Employing a multidisciplinary methodology that integrates literary analysis, psychological criticism, and cultural studies, the article demonstrates that The Virgin Suicides not only portrays individual tragedy but also critiques the societal forces and existential dilemmas underlying contemporary experiences of despair. Additionally, the article incorporates various authors’ perceptions, highlighting the diverse critical responses that have contributed to the understanding of the text’s thematic complexity.